The effects of stocking density on the growth perfomance, survival and feed conversion ratio of nile tilapia (orechromise niloticus) fry reared in conccrete tanks. - Alifa, Stanley (Midlands State University, 2021)
The study was conducted to evaluate the effect of different stocking densities on growth performances, survival rate and feed conversion ratio on the production potential of Nile tilapia fry (Oreochromis niloticus) reared in concrete tanks for 30 days from 10 November to 8 December 2018 at Lake Harvest Aquaculture, Kariba. A total of 120 000 fry (0.02 ± 0.002g) were collected, weighed and stocked in 16 tanks (each of 3.2 m² size) at four stocking densities of 3000 fry/ tank (T1), 6000 fry/ tank (T2) and 9000 fry/tank (T3) and 12000 fry/tank (T4). Each stocking density was replicated four times using a completely randomized design. Fry were fed with 17α- methyl testosterone hormone mixed with formulated feed 6 times a day at an initial rate of 15% of their body weight and adjusted to 10% of their body weight towards the end of experiment. Water quality parameters were monitored and found to be within suitable range for freshwater aquaculture. At the end of trial period, One -Way (ANOVA) using SPSS was used to test for significant variations (P<0.05).There were significant differences for growth parameter across all stocking densities. All growth measures were inversely proportional to stocking density. Weight gains were 1.03 ± 0.22g, 0.92 ± 0.08g, 0.65 ± 0.36g and 0.48 ± 0.46g for T1 to T4 respectively. Daily weight gains were 0.34 ± 0.0007g, 0.30 ±0.0002g, 0.22 ±0.0012 g and 0.16 ±0.0015g from T1 to T4 respectively. Specific growth rates per day were 0.13 ± 0.0007%, 0.13 ± 0.000, 0.12 ± 0.0018% and 0.11 ± 0.0029% from T1 to T4 respectively. Survival was indirectly proportional to stocking density. The highest survival rate was 81.55% ± 0.36 in T1 and the lowest survival was 55.17% ± 1.98 in T4. Increase in FCR was directly proportional to increase in stocking density .FCR was best in T1 with mean of 1.08 ±0.22.The worst FCR was found in T4 with an average of 2.26 ± 0.19. Cost based analysis showed highest feed loss directly proportional to stocking density. The lowest feed loss was 0.82 grams in T1. Feed loss increased across all treatments to 10.23 in T4. Net profit was highest in T2 followed by T1, T3 and lowest in T4.The study concluded that stocking 6000 fry per tank is beneficial for optimum growth, survival and good feed conversion ratio and farmers can stock 6000 fry in 3.2 m² concrete tanks for beneficial and optimum production of fry.